2004
DOI: 10.1074/jbc.m407570200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the C-terminal Proline-rich Motif of G Protein-coupled Receptor Kinases in Recognition of Activated Rhodopsin

Abstract: G protein-coupled receptor kinases (GRKs) are a family of serine/threonine kinases that phosphorylate many activated G protein-coupled receptors (GPCRs) and play an important role in GPCR desensitization. Our previous work has demonstrated that the C-terminal conserved region (CC) of GRK-2 participates in interaction with rhodopsin and that this interaction is necessary for GRK-2-mediated receptor phosphorylation (Gan, X. Q., Wang, J. Y., Yang, Q. H., Li, Z., Liu, F., Pei, G., and Li, L. (2000) J. Biol. Chem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…The sequence has one more distinguished region, the threonine/proline-rich motif, that is found also in other metazoan receptors (34). In the present study, the LPS-interacting protein was shown to bind LPS in a specific manner; no effect of the recombinant protein could be seen on cell-cell and celltissue adhesion.…”
Section: Discussionmentioning
confidence: 60%
“…The sequence has one more distinguished region, the threonine/proline-rich motif, that is found also in other metazoan receptors (34). In the present study, the LPS-interacting protein was shown to bind LPS in a specific manner; no effect of the recombinant protein could be seen on cell-cell and celltissue adhesion.…”
Section: Discussionmentioning
confidence: 60%
“…For GRK2, the High Q column simply acts as a prefilter for the removal of contaminants, including other protein kinases (Benovic, Mayor, Staniszewski, Lefkowitz, & Caron, 1987; Gan et al, 2004; Sterne-Marr et al, 2009). This property applies to GRK5 and GRK6, but not to GRK1 or GRK4α, which bind to both cation and anion exchangers (Ohguro et al, 1996; Premont et al, 1996; Sallese et al, 1997).…”
Section: Expression and Purification Of Grksmentioning
confidence: 99%
“…The presence of ionic interactions between GRK2 and its substrate is also supported by the observation that GRK2-mediated receptor phosphorylation is inhibited by salt (30). An additional region that has been implicated in GRK2⅐GPCR interaction is a proline-rich motif just aminoterminal to the nucleotide gate (31). Point mutations in this region not only disrupted the interaction of GRK2 with rhodopsin but also abolished the ability of GRK2 to phosphorylate rhodopsin.…”
Section: Figmentioning
confidence: 99%